Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Membeli Ikan Hias Perairan Sungai Batanghari di Kota Jambi - Asmaida Asmaida (Universitas Batangahari Jambi, 2022)
The Batanghari River is potential as a producer of ornamental fish and fish to be consumed. Ornamental fish originating from Batanghari River are relatively desired by consumers including botia fish, white stem susur, simancung and others. This research was located at TAC Market and Sarang Aquatic in Jambi City, which had the purpose to describe the characteristics of ornamental fish consumers, the purchase decision process, as well as to to analyze the influence of product factors (X1), location (X2), price (X3), promotion (X4), Beauty value (X5), lifestyle (X6), and social Status (X7) on the decision in buying ornamental fish in Jambi City (Y). The data collection method were carried out by questionnaires, interviews and observations. The total sample of 25 respondents was determined by the linear time function method. The data obtained were analyzed by that based on the characteristics of consumers, those who purchased ornamental fish were dominated by men with an age more than 24 years, Bachelor education level, entrepreneur dominance work, and an average income level of Rp.7,630,769. The step of needed evaluation, reasons or motivations of consumers to buy ornamental fish because ornamental fish products emphasize on the color, pattern, attractive shape and size, the clean and comfortable place, affordable prices according to its quality, social media promotions system beneficial for beauty and could calm the mind, could be collected and maintained for lifestyle. The results of the analysis in this study showed that the data was normally distributed. There was no both multicollinearity between independent variables in the multiticolinierity test and heteroskedasticity. It was found that there was no autocorrelation between the observational data in autocorrelation test, because null hypothesis (Ho) was accepted and alternative hypothesis (Ha) was rejected. the equation resulting in multiple linear regression analysis was Y= -0.239 +1.113X1 -0.520X2 +0.438X3 +0.105X4 -0.149X5 +0.295X6 +0.008X7 +e. The statistical tests showed that the coefficient of determination was 0.817, which means the influence of independent variables of 81.7%, while the remaining 18.3% was influenced by other factors that were not included in the study. F-test, resulted that the F calculated (16.303) > the critical F value (2.62) then null hypothesis (H0) was rejected or the independent variable simultaneously affected the dependent variable and the significant value was 0.000 < 0.05 so that the analysis results could be said to be significant or reliablet-test indicated that there were three variables that had a partially significant effect, namely the product variable (X1) for the calculated t value (8.647) > t critical value (2.112) and the degree of significance was 0.000 < 0.05. Place variable (X2) because the calculated t value (2.659) >t critical (2.112) and its significance level was 0.017<0.05. Price variable (X3) because the calculated t value (2.112) = t critical value (2.112) and its significance level was 0.050 = 0.05. Lifestyle variable (X6) because the calculated t value (2.190) > t critical value (2.112) and the significance level was 0.043 < 0.05.